2020
DOI: 10.1038/s41598-020-77028-8
|View full text |Cite
|
Sign up to set email alerts
|

PRMT1 inhibition induces differentiation of colon cancer cells

Abstract: Differentiation therapy has been recently revisited as a prospective approach in cancer therapy by targeting the aberrant growth, and repairing the differentiation and cell death programs of cancer cells. However, differentiation therapy of solid tumors is a challenging issue and progress in this field is limited. We performed High Throughput Screening (HTS) using a novel dual multiplex assay to discover compounds, which induce differentiation of human colon cancer cells. Here we show that the protein arginine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 64 publications
(90 reference statements)
2
10
0
Order By: Relevance
“…GSK3368715 targets these three PRMTs at similar IC50 (18) whereas PRMT6 and PRMT8 are more sensitive than PRMT1 to MS023 (17). We found that both inhibitors decrease cell viability and the growth of colonies in MDA-MB-468 cells aligning with previous studies in other cancer cell lines (18,(50)(51)(52). Together, we found that PRMT1 and its enzymatic activity are required for BC cell survival; however, we cannot rule out the influence of PRMT6 activity when using these inhibitors in our BC cell lines.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…GSK3368715 targets these three PRMTs at similar IC50 (18) whereas PRMT6 and PRMT8 are more sensitive than PRMT1 to MS023 (17). We found that both inhibitors decrease cell viability and the growth of colonies in MDA-MB-468 cells aligning with previous studies in other cancer cell lines (18,(50)(51)(52). Together, we found that PRMT1 and its enzymatic activity are required for BC cell survival; however, we cannot rule out the influence of PRMT6 activity when using these inhibitors in our BC cell lines.…”
Section: Discussionsupporting
confidence: 88%
“…However, there are two major differences between the two studies: (i) we engrafted tumors derived from MDA-MB-468 cells in contrast to Fedoriw et al, who directly injected these cells into the mice, (ii) we used a lower inhibitor dose (80mg/kg) as compared to them (150mg/kg) (18). Type I PRMT inhibitors have also been shown to decrease tumor growth in other cancer types such as lymphoma (18), pancreatic (18,34), hepatocellular carcinoma (52) and colon (51,59) cancer. Therefore, targeting type I PRMTs could represent a new treatment strategy in various cancer types, including BC.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these results, the type of interaction was defined using the Chou-Talalay method ( Figure 3 ) [ 26 ]. The most prominent effect was observed after combination treatment in HT-29 cells, which represent aggressive colon cancer cells [ 27 ]. At most combined concentrations, cell growth was reduced to a value below 0.5 (fa > 0.5; fa—fraction of the cells affected) in comparison to the control; untreated cells and the combined treatment were significantly more potent than individual treatments.…”
Section: Resultsmentioning
confidence: 99%
“…In this condition, we observed a similar reduction in tumor growth by using a reduced inhibitor dose (80 mg/kg in our study vs. 150 mg/kg [ 19 ]). Type I PRMT inhibitors have also been shown to decrease tumor growth in other cancer types such as lymphoma [ 19 ], pancreatic [ 19 , 38 ], hepatocellular carcinoma [ 66 ], and colon [ 64 , 67 ] cancers. Therefore, targeting type I PRMTs could represent a new treatment strategy in various cancer types, including BC.…”
Section: Discussionmentioning
confidence: 99%